A high-nuclearity isopolyoxotungstate based manganese cluster: one-pot synthesis and step-by-step assembly. Issue 43 (11th May 2018) - Zhang, Chao; Zhang, Mengrui; Shi, Hongyu; Zeng, Qingdao; Zhang, Dongdi; Zhao, Yaqing; Wang, Yuan; Ma, Pengtao; Wang, Jingping; Niu, Jingyang
Abstract : A high-nuclearity manganese–tungsten supercluster Na8 H32 [{Mn IV 24 Mn III 12 O28 (H2 O)23 }2 (W24 O120 )2 ]·66H2 O (Mn72 W48 ) has been successfully synthesized and its formation mechanism is investigated by ESI-MS. Abstract : A manganese(iii, iv )–tungsten(vi ) supercluster based on 72 manganese ions (48 Mn IV and 24 Mn III ) and 48 tungsten(vi ) centers [{Mn IV 24 Mn III 12 O28 (H2 O)23 }2 (W24 O120 )2 ] 40− has been prepared from the carboxylic Mn12 cluster. Its structure comprises two unprecedented cage-like Mn36 W24 cores linked via two Mn–O–W bonds, leading to a Mn72 W48 assembly. The inorganic synthetic mechanism was investigated through different synthesis methods and comprehensive ESI-MS tests.